Consumo via dispositivos móveis: um estudo sobre a aceitação dos consumidores para com o Mobile Commerce à luz da teoria do valor percebido - Souza, Dayvisson Emanoel Silva de (2017)
Due to the popularization of smartphones and improvements in mobile internet services, a new way of buying goods and acquiring services online has been gaining new adepts. This innovation in online trading is the mobile commerce. In m-commerce, people use their mobile devices to connect to the internet and through it they can consume the goods and services that suit them. However, there is still a significant portion of people who have not yet had an experience with this new context. Thus, this study aimed to understand how perceived value contributes to people's intention to adopt m-commerce. Also, understanding which factors precede and influence the shaping of perceived value also constitutes an objective of the present research. In a quantitative way, the survey method was applied through a structured questionnaire, disseminated in social networks, which generated a snowball effect and allowed the collection of 452 valid questionnaires. Statistical analysis was performed using the softwares SPSS and R. From an exploratory analysis of the data (ANOVA), it was possible to observe a significant difference in the responses between two groups of the sample: 1) people who had some experience with m-commerce and 2) those who have never made purchase through a cell phone. Thus, it was decided to carry out three analyzes, a global one, involving all questionnaires collected, one specific for the group of those who already bought via m-commerce and another for the group of those who never bought via mcommerce. In the overall analysis, seven of the nine background factors tested for influence on perceived value had their hypotheses accepted: perceived utility, perceived ease of use, relative advantage, compatibility, pleasure, perceived safety, and perceived cost. Interesting results emerged in the specific analyzes, such as the complexity construct that proved to be significant for the formation of the perceived value in the group that never bought via mobile phone, and the relative advantage that proved to be influential in the context of those who had some experience with m-commerce, but was rejected for those who have not yet.